Women’s Identity in the Digital Islam Age: Social Media, New Religious Authority, and Gender Bias - Ahmad Muttaqin (P3M STAIN Kudus, 2020)
This paper discusses the phenomenon of religious lectures on social media that are gender-biased. The gender-biased religious lectures delivered in social media by some famous figures perpetuate the discrimination against women in Indonesia. This research answers how and why the religious lectures with gender-biased theme appear massively on social media. By using a qualitative method and feminist approach, the study focuses on the religious preachers on the new social media. This study shows that the large amounts of lectures with the gender-biased theme in social media are inseparable from the role of the promotional accounts. It shares videos of gender-themed propaganda massively and attractively to attract many visitors and followers of these accounts. This study reveals that the massive religious lectures with gender bias on social media are not only dealing with the textual understanding of religious texts but also a matter of the religious commodification. The actors of business could determine the massively particular religious discourse on social media.